Teaching Global Ethical Standards: A Case and Strategy for Broadening the Accounting Ethics Curriculum - Tweedie, Dale; Dyball, Maria Cadiz; Hazelton, James; Wright, Sue (2013)
This paper advocates inclusion of a wider set of ethical theories into the accounting canon. We find that the mainstream accounting curriculum does not adequately engage with non-Western ethical theories or contemporary Western ethical thought, as evidenced by the ethics content of core accounting texts and the International Federation of Accountants’ ethics publications. We suggest adopting a ‘thematic’ approach to teaching ethics as an integrated part of accounting curricula. This approach addresses two competing principles implicit in International Education Standard 4: (i) that all accountants need to be educated to meet global ethical standards, and (ii) that teaching ethics should accommodate ethical traditions and practices that could vary between nations and cultures. The thematic approach we propose requires less additional space within existing accounting curricula and less additional preparation by accounting educators than the alternative approach of teaching substantive ethical theories from a sufficiently diverse range of cultures and traditions. The paper also provides exemplars of this thematic approach to teaching ethics in accounting.
Keywords: Non-Western ethics; IFAC; Globalisation; Confucianism; codes of ethics; accounting education